2020
DOI: 10.1109/jphot.2020.3010344
|View full text |Cite
|
Sign up to set email alerts
|

Angular Color Uniformity Enhancement for Color-Mixed LEDs by Introducing a Diffusing Coating Layer

Abstract: In this study, a simple and low-cost method is proposed to enhance angular color uniformity (ACU) of color-mixed light-emitting diodes (cm-LEDs) by introducing a diffuse coating layer. Optical models of the proposed cm-LEDs packaging modules were constructed by Monte Carlo ray-tracing simulation. The simulation results demonstrate the ACU enhancement of the cm-LEDs packaging modules with the application of the diffuse coating layer on the reflection cup. Owing to the strong light scattering and diffuse reflect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 31 publications
0
1
0
Order By: Relevance
“…Using only red phosphor is not an optimal approach to get better light-dispersion uniformity. Studies showed that the scattering in the LED package is one of the critical factors influencing the uniformity of angular light dispersion [13][14][15]. Thus, the study employs SiO 2 particles at nano-size as scattering regulators in the phosphor layer of the WLED.…”
Section: Introductionmentioning
confidence: 99%
“…Using only red phosphor is not an optimal approach to get better light-dispersion uniformity. Studies showed that the scattering in the LED package is one of the critical factors influencing the uniformity of angular light dispersion [13][14][15]. Thus, the study employs SiO 2 particles at nano-size as scattering regulators in the phosphor layer of the WLED.…”
Section: Introductionmentioning
confidence: 99%